(untitled) (Texas Journal of Medical Science, 2023)
The possibilities of transperineal (transperineal) ultrasonic examination of the prostate gland in it is various pathological conditions were investigated. The analysis included ultrasound data of 92 male patients with various pathologies of the prostate gland in the period from 2018 to 2022. Patients underwent an ultrasound examination of the pelvic organs, including a transabdominal examination and, subsequently, a transperineal examination. Transabdominal examination was not possible in the presence of a postoperative wound, after surgery on the bladder, the presence of drainage, inflammation in the suprapubic region, the patient’s obesity, and the presence of flatulence. Empty or empty bladder due to bladder failure. A large body weight and a large fat layer on the abdomen also made it difficult to examine the prostate gland. A visual comparison of the transabdominal and transperineal ultrasound methods for examining the prostate gland in its various pathological conditions is presented.